Pemahaman Masyarakat Desa Sebauk Terhadap Undang-Undang Informasi Transaksi Elektronik - Jon Hendri; Ambo Ako (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
The birth of Law Number 11 the Year 2008 concerning Electronic Transaction Information has a broad impact on the development of the community, of course, this has become a lesson for the public to not be ensnared by criminal acts. The purpose of this research is to find out about the understanding of village communities as the Information Law on Electrochemical Transactions. The results of the research of the authors found that the level of understanding of the people of Sebauk Village, Bengkalis District was lacking in the Information and Electronic Transaction Law. Of the 87 respondents, there were 69 respondents or 79% answered lack of understanding, 14 respondents or 16% answered did not understand at all, 4 respondents or 5% answered understood about the Information and Electronic Transaction Law and the rest no respondents showed an understanding of the Act -The law.